Study of endometrium in abnormal uterine bleeding at Patan Academy of Health Sciences, Patan Hospital Nepal - R.C, Laxmi (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction:Abnormal uterine bleeding (AUB) is considered as one of the most common and challenging problem presenting to the gynecologist. Establishing a cause of AUB is important, as medical therapy is effective in managing abnormal bleeding in most cases and should be attempted prior to surgical management. Endometrial biopsy is a safe and effective diagnostic step in evaluation of endometrium after ruling out any medical causes. The objective of this study is to evaluate the different histopathological patterns of the endometrial biopsy specimens in women presenting with AUBat Patan Hospital. Method: A two year retrospective study of AUB covering the year 2068 to 2069 . Patients charts were retrieved from the medical record section and reviewed. Result: The most common age group presenting with AUB was 41-50 years 58(49.1%).Among these patients,normal physiological patterns 62 (52.5%) with secretory endometrium(24.6%), proliferative endometrium 29 (22.9%) and menstrual phase 6 (5.1%) were observed. The commonest pathology irrespective of the age group was disordered proliferative pattern 23 (19.5%). Othercauses identified were endocervical polyp 8 (6.8%), hormonal effect 5 (4.2%), atrophic endometrium 5 (4.2%),endometrial carcinomas 5 (4.2%), complications of pregnancy 3 (2.5%), endometrial hyperplasias 3 (2.5%), endometritis 3 (2.5%) and endometrial polyp 1 (0.8%). Conclusion:Histopathological variations of the endometrium can detect the cause of the disorders taking into account the age and phase of a menstrual cycle. Timely evaluation of AUB by histopathology can be life saving diagnostic tool for early management.